2013
DOI: 10.11113/jt.v61.1620
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Effects of Light Rail Transit (LRT) System on the Property Values in the Klang Valley, Malaysia: A Hedonic House Price Approach

Abstract: This study investigates the increased value of land in the form of house prices as a result of improved accessibility owing to the construction of Light Rail Transit (LRT) systems. Kelana Jaya Line LRT system is chosen as the case study in this research. Hedonic house price modelling is employed to estimate the effects of the LRT system on the prices of the house that are located within the radius of two kilometres from the Kelana Jaya LRT stations. Selling prices, structural attributes, land use and socio-eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 29 publications
1
17
0
3
Order By: Relevance
“…However, some studies merely concentrate on certain building parameters such as the effects of green spaces in contributing the property prices [10,16], whereas Cellmer [3] put interests only on the effect of noise intensity. Other than the structural and locational variables, the socio demographic, socio economic and social variables where considered by others in their work [4,7]. In addition to the structural variables, Lehner [12] concentrate on the locational variables represented by the distances to the point of interests, POIs (i.e.…”
Section: Model Testmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies merely concentrate on certain building parameters such as the effects of green spaces in contributing the property prices [10,16], whereas Cellmer [3] put interests only on the effect of noise intensity. Other than the structural and locational variables, the socio demographic, socio economic and social variables where considered by others in their work [4,7]. In addition to the structural variables, Lehner [12] concentrate on the locational variables represented by the distances to the point of interests, POIs (i.e.…”
Section: Model Testmentioning
confidence: 99%
“…The distances to nearest freeway, and distances to nearest interstates both have negative effect [1]. Nevertheless, there is positive relationship between the existence of the light rail transit (LRT) system and house prices [4,7]. It was found that the longer the distances to the central business district (CBD), or to top schools may incur price discount in the real property.…”
Section: Assessment Of the Building Variablesmentioning
confidence: 99%
“…Syabri (2011) grasped the influence of railway stations on residential property values in Indonesia using a spatial hedonic approach. Dziauddina et al (2013) investigated the increased land value (in the form of house prices) as a result of improved accessibility owing to the construction of Light Rail Transit (LRT) systems in Klang Valley, Malaysia. With the network accessibility indicator proposed in Jang et al (2000) as a reference, the present study will propose "accessibility to destination stations" as a new indicator that quantitatively evaluates the convenience of each station.…”
Section: Related Workmentioning
confidence: 99%
“…Alguns pesquisadores já buscaram identi"icar a contribuição e cada uma dessas dimensões na valorização de imóveis comercializados. São elas: densidade (W. Li et al, 2014), diversidade (Shen e Karimi, 2017;Song e Knaap, 2004), desenho urbano, acessibilidade ao destino e distância ao transporte público (Cervero e Kang, 2011;Dziauddin et al, 2013;Munoz-Raskin, 2010;Rodriguez e Mojica, 2009). Alguns estudos ainda incluem a administração da demanda por viagem como uma sexta dimensão.…”
Section: Caminhabilidade E O Mercado Imobiliáriounclassified